Investor Attention and Stock Market Volatility - Andrei, Daniel; Hasler, Michael (Review of Financial Studies, 2015)
We investigate, in a theoretical framework, the joint role played by investors' attention to news and learning uncertainty in determining asset prices. The model provides two main predictions. First, stock return variance and risk premia increase with both attention and uncertainty. Second, this increasing relationship is quadratic. We empirically test these two predictions, and we show that the data lend support to the increasing relationship. The evidence for a quadratic relationship is mixed. Overall, our study shows theoretically and empirically that both attention and uncertainty are key determinants of asset prices.